The PERMA Model in Higher Education: A Sequential Explanatory Mixed-Methods Study of Well-Being Among Teacher Education Students - Nadia Aulia Nadhirah; Popy Mayasari Afendy; Ahman; Sudaryat Nurdin Akhmad; Syamsu Yusuf; Ilfiandra (Department of Guidance and Counseling, FIP, Undiksha, 2025)
The global teacher shortage crisis, marked by high attrition rates within the first five years of service, highlights the importance of fostering flourishing in teacher professional education. This study aims to examine how the PERMA dimensions of flourishing are manifested among Indonesian teacher education students to generate culturally responsive and contextually grounded insights that support teacher readiness and retention. Using a sequential explanatory mixed-methods design, data were collected from 312 students across faculties and semesters. Phase 1 employed MANOVA to examine demographic variations in PERMA scores using validated instruments. Phase 2 involved thematic analysis of 24 in-depth interviews to explore students’ lived experiences of flourishing. Joint displays and meta-inferences were used to integrate quantitative and qualitative findings. Results showed no significant demographic differences in PERMA scores, challenging assumptions about variation based on gender, faculty, or semester. However, qualitative findings revealed culturally nuanced expressions of flourishing, including collective emotional experiences, relational engagement, service-oriented meaning-making, and communal celebration of individual success. These insights suggest that while the PERMA framework remains structurally relevant, its expression in collectivist cultures like Indonesia reflects unique cultural pathways. This study contributes to the global discourse on positive psychology by highlighting the need for culturally grounded applications of flourishing. The findings offer a foundation for developing teacher education programs that are both evidence-based and culturally responsive, enhancing well-being and long-term commitment among future educators.